The Effect of Digital Literacy, Product Innovation, Business Resilience, and Entrepreneurial Orientation on the Sustainability of Culinary MSMEs in the Kemiling Area, Bandar Lampung - Ahmad Munir; Rahyono; Hiro Sejati (Yayasan Multidimensi Kreatif, 2026)
This study aims to empirically examine the partial and simultaneous effects of digital literacy, product innovation, business resilience, and entrepreneurial orientation on the sustainability of culinary Micro, Small, and Medium Enterprises (MSMEs) in the Kemiling Area, Bandar Lampung. Grounded in the Resource-Based View (RBV) theory, this research employs a quantitative approach with a descriptive and associative survey design. Primary data were collected through Likert-scale questionnaires distributed to 109 valid respondents who are culinary MSME owners, and the data were subsequently analyzed using multiple linear regression. The findings reveal that digital literacy and product innovation do not have a significant partial effect on MSME sustainability, indicating that current technological and creative practices are still applied at a basic operational level rather than as strategic long-term drivers. In contrast, business resilience and entrepreneurial orientation exert a positive and significant partial impact, proving to be critical pillars for operational stability and adaptability in dynamic markets. Simultaneously, all four variables significantly influence MSME sustainability, accounting for 66.3% of the variance. The study concludes that while resilience and a proactive entrepreneurial mindset are dominant survival factors, culinary MSMEs must elevate their digital and innovative capabilities to achieve long-term sustainable growth and competitive advantage.